Oscar S. Straus papers - Straus, Oscar S. (Oscar Solomon), 1850-1926.; Oscar S. Straus Memorial Association
Correspondence, diaries, speeches, writings, notebooks, legal records, pamphlets, clippings, scrapbooks, photographs, memorabilia, and other papers relating chiefly to Straus's service as U.S. minister and ambassador to the Ottoman Empire (Turkey), U.S. secretary of commerce and labor, and member of the Permanent Court of Arbitration, Hague, Netherlands. Also documents his activities with the National Civic Foundation, New York (State) Public Service Commission, League to Enforce Peace, and the Industrial Conference held in Washington, D.C., 1919-1920. Subjects include a visit to Egypt in 1888, railway wage negotiations, religious liberty in the Ottoman Empire, Romania, Russia, World War I, and Louis Lavanburg. Includes records (1927-1954) of the Oscar S. Straus Memorial Association, Straus (Strauss) family papers, and a privately printed autobiography of Straus's brother, Isidor Straus. Correspondents include Robert Bacon, John Barrett, Thomas F. Bayard, Nicholas Murray Butler, Andrew Carnegie, Grover Cleveland, Calvin Coolidge, Ralph M. Easley, James Rudolph Garfield, Lloyd Carpenter Griscom, Warren G. Harding, Benjamin Harrison, John Hay, Lee Kohns, Robert Lansing, William Loeb, William McKinley, Adolph S. Ochs, George Foster Peabody, Theodore Roosevelt, Elihu Root, Isidor Straus, Nathan Straus, William H. Taft, and Woodrow Wilson.
Microfilm of scrapbook selections available
Library of Congress Rare Book and Special Collections Division.
Attorney, businessman, public official, diplomat, U.S. secretary of commerce and labor, and author.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bacon, Robert, -- 1860-1919 -- Correspondence; Barrett, John, -- 1866-1938 -- Correspondence; Bayard, Thomas F. -- 1828-1898 -- Correspondence; Butler, Nicholas Murray, -- 1862-1947 -- Correspondence; Carnegie, Andrew, -- 1835-1919 -- Correspondence; Cleveland, Grover, -- 1837-1908 -- Correspondence; Coolidge, Calvin, -- 1872-1933 -- Correspondence; Easley, Ralph M. -- 1858- -- Correspondence; Garfield, James Rudolph, -- 1865-1950 -- Correspondence; Griscom, Lloyd Carpenter, -- 1872-1959 -- Correspondence; Harding, Warren G. -- 1865-1923 -- Correspondence; Harrison, Benjamin, -- 1833-1901 -- Correspondence; Hay, John, -- 1838-1905 -- Correspondence; Kohns, Lee, -- 1864-1927 -- Correspondence; Lansing, Robert, -- 1864-1928 -- Correspondence; Lavanburg, Louis; Loeb, William, -- 1866-1937 -- Correspondence; McKinley, William, -- 1843-1901 -- Correspondence; Ochs, Adolph S. -- 1858-1935 -- Correspondence; Peabody, George Foster, -- 1852-1938 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Root, Elihu, -- 1845-1937 -- Correspondence; Straus, Isidor, -- 1845-1912.; Straus, Isidor, -- 1845-1912 -- Correspondence; Straus, Nathan, -- 1848-1931 -- Correspondence; Taft, William H. -- 1857-1930 -- Correspondence; Wilson, Woodrow, -- 1856-1924 -- Correspondence; Strauss family; New York (State). -- Public Service Commission; United States. -- Department of Commerce and Labor; League to Enforce Peace (U.S.); National Civic Federation; Permanent Court of Arbitration; Arbitration (International law); Diplomatic and consular service, American -- Turkey; Industrial relations -- United States; Labor policy -- United States; Freedom of religion -- Turkey; Wages -- Railroads -- United States; World War, 1914-1918.; Egypt -- Description and travel; Romania; Russia; Turkey -- Foreign relations -- United States; Turkey -- History -- Ottoman Empire, 1288-1918.; United States -- Economic policy; United States -- Foreign relations -- Turkey; Authors; Businessmen; Cabinet officers; Diplomats; Lawyers